159k views
4 votes
Given the following table, find the rate of change between f(-1) and f(2). x -1 0 1 2 3 f(x) -2 -1

User Imthegiga
by
4.5k points

2 Answers

5 votes

Answer:

7 over 12

Explanation:

The table is incomplete, so I will answer the question in general terms. The rate of change between f(-1) and f(2) is computed as follows:

rate of change = [f(2) - f(-1)]/[2 - (-1)] = [f(2) - f(-1)]/3

To complete the calculation you need to replace the values of the function at x = 2 and x = -1, and compute the result.

User Futtta
by
5.2k points
2 votes

Answer:

[f(2) - f(-1)]/3

Explanation:

The table is incomplete, so I will answer the question in general terms. The rate of change between f(-1) and f(2) is computed as follows:

rate of change = [f(2) - f(-1)]/[2 - (-1)] = [f(2) - f(-1)]/3

To complete the calculation you need to replace the values of the function at x = 2 and x = -1, and compute the result.

User Sonia
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.